Selection strategies within progenies of two Myracrodruon urundeuva Fr. All. populations - Silva Baleroni Guerra, Carla Renata [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP]; Soares Petrarolha da Silva, Cristina Lacerda [UNESP]; Oliveira Canuto, Daniela Silvia de [UNESP]; Costa Andrade, Joao Antonio da [UNESP]; Menezes Freitas, Miguel Luiz; Sebbenn, Alexandre Magno (Ipef-inst Pesquisas Estudos Florestais, 2009)
Myracrodruon urundeuva Fr. All, is a tree species threatened by human pressure. For this reason, this research aimed at evaluating the behavior of two populations of M. urundeuva in a heterogeneous plantation as a support for genetic ex situ conservation. Two progeny tests of M. urundeuva were evaluated. The tests were established in Selviria, MS in 1992 as a heterogeneous plantation, composed of 25 families from Aramina, SP and 25 from Selviria, MS. The following silvicultural traits were evaluated: DBH (Diameter at breast height), DMC (average diameter of crown), height (ALT), stern form (FOR) and survival (SOB). The results based on the REML/BLUP method, suggest that populations of M. urundeuva from Aramina and Selviria have a good adaptation to environmental conditions of Selviria. This became evident by the high survival rate. Genetic variation was higher in the Selviria population when compared to the Aramina population. By using multi-effect index (IME), it is possible to select progenies that can provide a good selection gain and high variation. In that case, a maximum Kf must be established. This condition yields a higher genetic gain in the Selviria than in the Aramina population.
Keywords: Aroeira; Multi-effect index; Genetic parameter; Quantitative genetics